Exploring the media representation of poverty in Darfur, Western Sudan - Mohamed, Elsir Ali Saad; Abasher, Mathani Hassan; Ibrahim Abdelaziz Ishag, Khalid; Al-Rached, Saleh Obaid; Alamin, Mohanad; Mohamed, Widad (Frontiers in Communication, 2026)
This research analyzes how media constructs narratives of poverty during the Darfur crisis in Sudan. It examines news coverage from international, regional, and local sources (2003–2022) to understand the dominant representational strategies, not to contrast them with a single “true” reality, but to uncover the specific political and ideological work they perform. Employing a triangulated methodology of qualitative content analysis, critical discourse analysis, and multimodal analysis, the study identifies recurring frames: a dominant “conflict-poverty” nexus, the portrayal of Darfuri civilians as helpless victims, and the characterization of aid organizations as heroic saviors. The analysis reveals how linguistic and visual strategies prioritize immediate emotional impact, often at the expense of historical and political context. By situating these findings within postcolonial and African media theory, the study argues that these representations are not mere distortions but active constructions that reflect and reinforce particular power dynamics. The paper concludes by discussing the implications of these representational patterns and suggests pathways for more reflexive and contextually-grounded journalism.